Ketepatan Alat Ukur dalam Evaluasi Pendidikan: Kajian Validitas Instrumen - Ariyanto Ariyanto; Achmad Rasyid Ridha (TSAQOFAH, 2026)
Although educational evaluation is an important component in determining the success of the learning process, the accuracy of evaluation results greatly depends on the quality of the measuring instrument used in the assessment process. Invalid instruments can produce inaccurate data, so evaluation results do not objectively reflect students’ abilities. This study aims to examine the accuracy of measuring instruments in educational evaluation from the perspective of instrument validity. This study used a library research method with a descriptive qualitative approach. Data were obtained from various literature sources in the form of books, scientific articles, and journals relevant to educational evaluation and instrument validity. The results of the review show that validity is the main determinant of the accuracy of educational evaluation results. Instruments that do not meet theoretical or empirical validity have the potential to cause assessment bias and errors in educational decision-making. Conversely, strengthening instrument validity can improve the objectivity, accuracy, and credibility of evaluation results. The conclusion of this study affirms that instrument validity is the main foundation for achieving the accuracy of measuring instruments in educational evaluation. These findings contribute to strengthening studies on educational measurement and provide practical implications for educators and instrument developers in preparing valid, objective, and accountable evaluation tools.